Transition to Academic Probation: A Phenomenological Inquiry - Deveyvon Espinosa; Jonelson Escandallo; Kristy Jane Muegna (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2023)
Academic probation implementation in higher education institutions aims to ensure that students are meeting academic standards and making satisfactory progress toward their degree or program requirements. It serves as a warning to students not meeting these standards that their academic performance needs improvement. Hence, the purpose of this study was to unveil the lived experiences of board program students who have undergone probation period. The study is qualitative research utilizing the phenomenological approach. This research used purposive sampling. The participating ten board program students were identified and divided equally for in-depth interviews and focus group discussion. The data gathered were analyzed through the use of coding and thematic analysis. Results revealed from responses regarding their experiences: (1) the feeling of self-doubt, (2) gained focus due to limited units, (3) fear of judgment, (4) being challenged to strive more, and (5) kept on blaming the self. In response to the challenges they have encountered, they emphasized the following coping mechanisms as essential: (6) gaining motivation from significant others, (7) managing time properly, (8) becoming optimistic, and (9) having an attitude of acceptance. Also, upon reflecting on their overall experiences, they highlighted the following insights: (10) never giving up, taking full responsibility amidst results, (11) challenging policy with a purpose, (12) making self-realizations, and (13) avoiding taking advantage. The results implied that there are certain interventions to be made within the institution to extend assistance to the students’ situations, such as tutorial sessions, and enhance the guidelines of the academic probation policy to strengthen collaboration with its stakeholders. This study is therefore deemed significant as this highly contributes to the body of knowledge related to academic probation policy implementation by higher education institutions.